How to do health services research in stroke: a focus on performance measurement and quality improvement - Cadilhac, Dominique A.; Fisher, Rebecca J.; Bernhardt, Julie (SAGE Publications, 2018)
The objective of this ‘How to’ research series article is to provide guidance on getting started in Health Services Research. The purpose of health services research is to contribute knowledge that can be used to help improve health systems and clinical services through influencing policy and practice. The methods used are broad, have varying levels of rigour and may require different specialist skills. This paper sets out practical steps for undertaking health services research. Importantly, use of the highlighted techniques can identify solutions to address inadequate knowledge translation or promote greater access to evidence-based stroke care to optimise patient outcomes.